Randomized controlled trial of Micro-Mobile Compression® on lactate clearance and subsequent exercise performance in elite male cyclists - San Millán I; Bing K; Brill C; Hill JC; Miller LE (Dove Medical Press, 2013)
Iñigo San Millán,1 Kristen Bing,1 Carrie Brill,1 John C Hill,1 Larry E Miller2 1University of Colorado School of Medicine, Aurora, CO, 2Miller Scientific Consulting, Inc, Arden, NC, USA Background: The purpose of this paper was to assess the feasibility of Micro-Mobile Compression® (MMC) on lactate clearance following exhaustive exercise and on subsequent exercise performance. Methods: Elite male cyclists were randomized to MMC (n = 8) or passive recovery (control, n = 8). MMC is incorporated into a sandal that intermittently compresses the venous plexus during non-weight bearing to augment venous return. On day 1, subjects performed a graded exercise test on a cycle ergometer followed by 60 minutes of seated recovery, with or without MMC. Blood lactate concentration ([La¯]) was measured during exercise and recovery. Subjects returned home for 3 more hours of seated recovery, with or without MMC. On days 2 and 3, subjects exercised to exhaustion in a fixed-load cycle ergometer test at 85% peak power and then repeated the day 1 post-exercise recovery procedures. Lactate clearance data after the time to exhaustion tests on days 2 and 3 were averaged to adjust for interday variation. Results: On the day after MMC or control recovery, mean time to exhaustion was 15% longer (mean difference, 2.1 minutes) in the MMC group (P = 0.30). The standardized mean difference of MMC for time to exhaustion was 0.55, defined as a moderate treatment effect. Following the graded exercise test, area under the 60-minute lactate curve was nonsignificantly lower with MMC (3.2 ± 0.4 millimolar [mM]) versus control (3.5 ± 0.4 mM, P = 0.10) and times from end of exercise to 4mM and 2mM were 2.1 minutes (P = 0.58) and 7.2 minutes (P = 0.12) shorter, although neither achieved statistical significance. Following time to exhaustion testing, the area under the 60-minute lactate curve was lower with MMC (3.2 ± 0.2 mM) versus control (3.5 ± 0.2 mM, P = 0.02) and times from end of exercise to 4mM and 2mM were 4.4 minutes (P = 0.02) and 7.6 minutes (P < 0.01) faster. The standardized mean difference of MMC on most lactate clearance parameters was >0.8, defined as a large treatment effect. Conclusion: MMC yields large treatment effects on lactate clearance following high-intensity exercise and moderate treatment effects on subsequent exercise performance in elite male cyclists. Keywords: cycling, graded exercise test, recovery, time to exhaustion, venous return